2015
DOI: 10.7171/jbt.15-2604-002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Extraction of Viral and Bacterial Nucleic Acids for Molecular Diagnostic Applications

Abstract: Molecular detection of microbial pathogens in clinical samples requires the application of efficient sample lysis protocols and subsequent extraction and isolation of their nucleic acids. Here, we describe a simple and timeefficient method for simultaneous extraction of genomic DNA from gram-positive and -negative bacteria, as well as RNA from viral agents present in a sample. This method compared well with existing bacterial-and viralspecialized extraction protocols, worked reliably on clinical samples, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The first protocol was conducted using the PowerViral ® Environmental RNA/DNA Isolation Kit (MoBio samples), and the other protocol was the "Copurification" protocol of the ZymoBIOMICS™ DNA/RNA Miniprep Kit (Zymo samples). Although we used the approach of Leite et al [30], who performed 2 cycles of 25-s agitation with a 5-s interval break, which they recommended to avoid possible degradation of nucleic acids and which was also reported by others [31,32], we improved the results of the MoBio and Zymo assays by performing the bead beating step at 4 • C and increasing the time to 5 min. Apart from the significant differences for the 5-min MoBio protocol compared with the 5-min Zymo protocol, the volume of the starting material for the MoBio extraction was 20% less than that for the Zymo kits (200 µL vs. 250 µL, respectively), and the number of steps of MoBio was fewer than that of Zymo, reducing the possibility of human error or contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The first protocol was conducted using the PowerViral ® Environmental RNA/DNA Isolation Kit (MoBio samples), and the other protocol was the "Copurification" protocol of the ZymoBIOMICS™ DNA/RNA Miniprep Kit (Zymo samples). Although we used the approach of Leite et al [30], who performed 2 cycles of 25-s agitation with a 5-s interval break, which they recommended to avoid possible degradation of nucleic acids and which was also reported by others [31,32], we improved the results of the MoBio and Zymo assays by performing the bead beating step at 4 • C and increasing the time to 5 min. Apart from the significant differences for the 5-min MoBio protocol compared with the 5-min Zymo protocol, the volume of the starting material for the MoBio extraction was 20% less than that for the Zymo kits (200 µL vs. 250 µL, respectively), and the number of steps of MoBio was fewer than that of Zymo, reducing the possibility of human error or contamination.…”
Section: Discussionmentioning
confidence: 99%
“…For Staphylococcus , as with other organisms that possess thick cell walls, specialized DNA-extraction methods are required 3942. If these methods are used, it has been shown that increased detection of Staphylococcus comes at the expense of microbial organisms with a fragile cell wall and viruses 43,44. Currently, there is no commercial nucleic acid-extraction kit that can simultaneously extract Gram-positive, Gram-negative, and viruses from the same sample.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no commercial nucleic acid-extraction kit that can simultaneously extract Gram-positive, Gram-negative, and viruses from the same sample. Kajiura et al44 proposed a method for achieving this goal through techniques that prevent the loss of smaller viral particles while still extracting Gram-positive bacteria. This has been successfully used on 300 archived clinical samples of respiratory origin.…”
Section: Discussionmentioning
confidence: 99%
“…can reduce the efficiency of DNA extraction, protocols should be optimized to the sample matrix 18 . Besides, the resistance to lysis of some bacteria, such as Gram-positive bacteria 19 , may reduce our ability to detect them, creating a bias toward more easily lysed genera. The microbial biomass in the lung is low compared to what is found in the digestive system 20 .…”
Section: Introductionmentioning
confidence: 99%